Local recurrence of breast cancer: conventionally fractionated partial external beam re-irradiation with curative intention - Janssen, S.; Rades, D.; Meyer, A.; Fahlbusch, F. B.; Wildfang, I.; Meier, A.; Schild, S.; Christiansen, H.; Henkenberens, C. (Strahlentherapie und Onkologie, 2018)
PURPOSE: To assess the outcome of breast cancer patients with local recurrence who underwent partial external beam re-irradiation (re-RT) either as part of a second breast-conserving therapy or following mastectomy. METHODS: Between 03/2004 and 10/2016, 83 breast cancer patients with local recurrence were treated with surgery followed by re-RT. The re-RT schedules were 45 Gy (1.8 Gy per fraction) administered either to the partial breast (n = 42) or mastectomy scar (n = 41). The patients and tumor characteristics predictive of local control, distant control, and survival (overall and breast-cancer specific) were evaluated by univariate and multivariate analyses. RESULTS: The median follow-up was 35 months (range 3-143 months). The median time interval between the first irradiation and re-RT was 117 months (range 16-357 months). The prognostic factors for favorable overall survival rates were younger age (p = 0.045), lower T‑category (p = 0.019), and N0 category (p = 0.005). N0 was also superior to N+ with respect to outfield recurrences (p = <0.001) and breast cancer-specific survival (p = 0.025). Acute and late skin toxicity was generally low (
EVALuna2:35729